3D mesoscopic investigation of the specimen aspect-ratio effect on the compressive behavior of coral aggregate concrete. (1st October 2020) - Wu, Zhangyu; Zhang, Jinhua; Yu, Hongfa; Ma, Haiyan
Abstract: To explore the specimen aspect-ratio (height-to-diameter ratio) effect on the compressive behavior of coral aggregate concrete (CAC), a three-dimensional (3D) mesoscale modelling approach with considerations of random shapes and distributions for aggregates was developed in the present study. Through the comparison of numerical and available test results, the reliability of the numerical approach for CAC cylinder specimen with various aspect ratios (2–6) was validated. The stress-strain relations, failure patterns and failure processes of CAC in compression were numerically simulated and discussed in succession. Finally, the aspect-ratio effect law on the uniaxial compressive strength of CAC was obtained and compared with that of ordinary concrete. The results indicate that the post-peak branch of the compressive stress-strain curve of CAC tends to steeper with the increase of specimen length, which corresponds to the localization behavior of concrete. In addition, when the height-to-diameter ratio exceeds 2–3, the length of failure zone is close to three times of the specimen diameter (100 mm). Distinctive failure characteristics of each components (i.e., coral aggregate, mortar and ITZ) in CAC with different lengths were presented, and it was found that there is a faster failure process in the shorter specimen and the cracks in the longer specimen would obliquely propagate in the lateral surface. Furthermore, it has been demonstrated that the uniaxial compressive strength of CAC is related to the specimen aspect-ratio, while it becomes insignificant when the aspect ratio exceeds 2.5–3. Graphical abstract: Image 1 Highlights: The specimen aspect-ratio effect on the compressive behavior of coral aggregate concrete. A three-dimensional (3D) random mesoscale modelling approach considering random shapes and distributions of aggregates. The compressive stress and strain behaviors, failure patterns and failure processes of CAC. The aspect-ratio effect law of uniaxial compressive strength.